Precisão do posicionamento RTK usando correções diferenciais transmitidas pelo sistema NTRIP (RBMC-IP) - Moreira, Antão Leonir Langendolff (2011)
The Global Navigation Satellite System (GNSS), in the last few years, has been supporting the development of mobile telephony and the expansion of electronic equipments (GNSS receivers) to promote a revolution in geodetic surveys in real time. In this context, it becomes important the technique of positioning Real Time Kinematic (RTK) with the use of differential corrections transmitted by the protocol named Networked Transport of RTCM via the Internet Protocol (NTRIP), from a reference station via Internet. It is aimed, in this research, the evaluation of the precision of this technique for different lengths of baseline, and also the use of different numbers of trace periods. Then, three-dimensional coordinates of 10 stations (DEM) were used, they were also located in three municipalities of Rio Grande do Sul, which were traced by the static post-processed (static PP) method, which helped as being a reference in comparison with technique RTK / NTRIP, that used the correlations of the Brazilian Network for Continuous Monitoring of the GNSS Systems in real time - (RBMC-IP). The results showed that there was resolution of the ambiguities in nine seasons at baseline greater than 54 km, and that the precision values showed no difference greater than 0.041 m in the horizontal component and 0.083 m in the vertical component. In addition, between the numbers of the tested periods (5,10,30, 60 and 120 periods) for the method RTK / NTRIP, the tested period that had the best average precision of the horizontal component was the 120 one (0.01 m), and for the vertical component was considered the five periods number as the most appropriated (0.02 m). Hence, it was proved the reliability of the technique RTK / NTRIP (RBMC-IP) in baselines of until 54 km, showing that it can be used for topographical surveys in areas with wireless Internet or cellular services such as GPRS, GSM and 3G.